2008
DOI: 10.5424/sjar/2008064-353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for glutenin and gliadins associated with quality in durum wheat (Triticum turgidum L. ssp. turgidum) landraces from Spain

Abstract: The allelic variation at seven prolamin loci involved in quality has been studied in a set of durum wheat landraces from all the Spanish regions where this crop has been traditionally cultivated. The genetic variability was higher than that found in other germplasm collections. All the loci, except Glu-B2, displayed a genetic variability higher than 0.62, with Glu-3 the most polymorphic. In total, five alleles were studied at Glu-A1, nine at Glu-B1, 15 at Glu-A3, 18 at Glu-B3, two at Glu-B2, and eight at Gli-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 23 publications
11
35
3
Order By: Relevance
“…At the Glu - B3 locus, the allele Glu - B3d was the most frequent (65%) which had a medium to weak dough properties (Cornish et al 1993; Luo et al 2001). For the Glu - A3 and Glu - B3 , our results were quite different from the Spanish durum landraces (Aguiriano et al 2008), in which they reported the predominance of allele a for both locus. Compared to bread wheat, durum wheat was less variable in glutenin alleles.…”
Section: Discussioncontrasting
confidence: 99%
“…At the Glu - B3 locus, the allele Glu - B3d was the most frequent (65%) which had a medium to weak dough properties (Cornish et al 1993; Luo et al 2001). For the Glu - A3 and Glu - B3 , our results were quite different from the Spanish durum landraces (Aguiriano et al 2008), in which they reported the predominance of allele a for both locus. Compared to bread wheat, durum wheat was less variable in glutenin alleles.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the collection was assessed for gliadin alleles at four loci: Gli-A1, Gli-B1, Gli-A2 and Gli-B2 . Gliadins were extracted from single seeds and fractioned using acid polyacrylamide gel electrophoresis (pH 3.1), according to Lafiandra and Kasarda [49], with their classification according to Riefolo et al [14], Boggini et al [50] and Aguiriano et al [51].…”
Section: Methodsmentioning
confidence: 99%
“…turgidum) landraces from 27 provinces were selected from the wheat collection maintained in the Plant Genetic Resources Centre at the Spanish National Institute for Agricultural and Food Research and Technology (CRF-INIA). The Bank number, local name, and geographical region of the landraces was described in Aguiriano et al (2008). This sample set was evaluated during two seasons (2001-2002 and 2003-2004) and at two N rates in 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The prolamin composition of the landraces was reported in Aguiriano et al (2008). HMW glutenin alleles at Glu-1, and B-LMW glutenin alleles at Glu-3 and Glu-B2 were identified with the nomenclature of Payne and Lawrence (1983) and Nieto-Taladriz et al (1997), respectively.…”
Section: Quality Evaluationmentioning
confidence: 99%